2006
DOI: 10.1111/j.1939-1676.2006.tb02833.x
|View full text |Cite
|
Sign up to set email alerts
|

CCNU in the Treatment of Canine Epitheliotropic Lymphoma

Abstract: This retrospective study examined the use of CCNU (1-[2-chloroethyl]3-cyclohexyl-1-nitrosurea) in 36 dogs with epitheliotropic lymphoma. Thirty-one (86%) dogs had the cutaneous form of disease, and 5 (14%) dogs had the oral form of disease. Nineteen (51%) dogs were treated with other chemotherapeutic agents before receiving CCNU. All dogs had detectable disease at the time CCNU therapy was initiated. Dogs received a median starting CCNU dosage of 70 mg/m2 (range, 50-100 mg/m2). The median number of treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 34 publications
6
95
2
2
Order By: Relevance
“…Other common adverse effects included hepatic and gastrointestinal toxicities, which were not unexpected based on the combination of drugs used in this protocol. Lomustine is known to cause hepatotoxicity in dogs, with reported rates of 83–86% . Twenty‐four dogs (59%) developed increases in ALT activity during this study, with 9 dogs having grade 3 or 4 increases.…”
Section: Discussionmentioning
confidence: 71%
“…Other common adverse effects included hepatic and gastrointestinal toxicities, which were not unexpected based on the combination of drugs used in this protocol. Lomustine is known to cause hepatotoxicity in dogs, with reported rates of 83–86% . Twenty‐four dogs (59%) developed increases in ALT activity during this study, with 9 dogs having grade 3 or 4 increases.…”
Section: Discussionmentioning
confidence: 71%
“…Hosoya et al 10 reported on 109 dogs treated with CCNU for a variety of cancers and found that 83% developed some increase in ALT activity over their starting result. Williams et al 2 reported on 36 dogs with cutaneous LSA treated with CCNU and found that 60% of dogs tested after treatment had increases in ALT activity, and 86% of dogs that had more than 1 dose of CCNU had increases in ALT activity. Given the high incidence of increases in liver enzyme activity in dogs receiving CCNU and the acute onset of severe increases noted in some patients, frequent liver‐specific laboratory testing should be considered during CCNU‐based therapy in these dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies reported that lomustine can be considered for the treatment of canine lymphoma in dogs [40], [41], [42], [43], although it induced common but not life-threatening toxicity [44].…”
Section: Discussionmentioning
confidence: 99%